Binder with self-repairing function and preparation method of silicon-based negative electrode of lithium ion battery
By using PVA-4FBA-PEI binder in the silicon-based anode of lithium-ion batteries, the problem of long self-healing response time is solved, and the rapid self-healing and mechanical performance is unified, effectively improving the cycle stability and capacity retention rate of the battery.
Patent Information
- Application Number
- CN202411901169.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-01
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing silicon negative electrode self-healing binder has a long self-healing response time during the cycle, and cannot effectively deal with the stress caused by volume expansion of silicon particles, resulting in silicon particles crushing and battery failure.
By mixing polyvinyl alcohol (PVA), 4-formylphenylboric acid (4FBA) and polyethyleneimine (PEI) in a specific proportion, the binder PVA-4FBA-PEI with self-healing function is formed, and it is used in the preparation of silicon-based anode of lithium-ion batteries. The binder achieves a rapid self-healing function through the locking structure of the double dynamic bond and the parallel movement of the polymer chain.
The binder can be completely repaired within 2 minutes, providing ultra-fast self-healing function, and at the same time improving the mechanical strength and flexibility of the binder, effectively inhibiting the crushing of silicon particles, maintaining the stability of the negative electrode structure and interface, and the capacity retention rate reaches more than 80%.
Smart Images

Figure CN119736065A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a silicon-based negative electrode of a lithium ion battery. Background Art
[0002] Silicon is considered to be one of the ideal negative electrode materials for high-energy lithium-ion batteries because of its large theoretical specific capacity, low lithium insertion potential and abundant sources. However, silicon negative electrodes will undergo large volume expansion / contraction during the cycle, resulting in huge stress, which will lead to severe particle crushing and pulverization. The binder of silicon-based negative electrodes plays a key role in long-term stability. By designing a suitable binder, the problem of poor electrochemical performance of silicon electrodes caused by large volume changes and low conductivity can be improved. At present, polyvinylidene fluoride (PVDF) and carboxymethyl cellulose (CMC) are often used as binders for silicon-based negative electrodes of lithium-ion batteries to alleviate volume changes because of their excellent mechanical properties and / or strong interaction with silicon. However, due to the poor plasticity, low stiffness and weak interaction between polyvinylidene fluoride and carboxymethyl cellulose and silicon particles and current collectors, they are not enough to adapt to the volume expansion of Si, which eventually leads to crushing, peeling and battery failure of silicon particles during the cycle. In contrast, self-healing adhesives make up for the shortcomings of traditional adhesives by spontaneously repairing the polymer breaks caused by the irreversible volume expansion of silicon particles, and maintain good electrical contact with the current collector during the charge and discharge process. The self-healing process is achieved by the rapid diffusion of polymer chains at a certain temperature to achieve reversible rupture and recombination of covalent bonds. From the perspective of mechanical stability, the entanglement of polymers with excellent plasticity and flexibility improves the tensile strength limit of the adhesive when it withstands the volume expansion of silicon particles. However, there is a competition between the mechanical strength and rapid self-healing time of the self-healing adhesive. This is because the entanglement of polymer chains enhances its mechanical properties but hinders the diffusion of chains, reducing the self-healing ability, thereby prolonging the response time of traditional self-healing adhesives to the volume expansion of silicon particles. Summary of the invention
[0003] The present invention aims to solve the technical problem of long self-repair response time of the existing self-repairing binder for silicon negative electrode, and provide a binder with self-repairing function and a preparation method of lithium ion battery silicon-based negative electrode.
[0004] The preparation method of the adhesive with self-repairing function of the present invention is carried out according to the following steps:
[0005] 1. According to the mass ratio of polyvinyl alcohol (PVA), 4-formylphenylboronic acid (4FBA) and polyethyleneimine (PEI) being (0.8-1.5):(0.07-0.085):(0.45-1.2), weigh polyvinyl alcohol (PVA), 4-formylphenylboronic acid (4FBA) and polyethyleneimine (PEI);
[0006] 2. Add the polyvinyl alcohol weighed in step 1 to deionized water, stir at a temperature of 75 to 80° C. for 2.5 to 3 hours to obtain a polyvinyl alcohol solution; add 4-formylphenylboric acid to ethanol, stir for 0.5 to 1 hour, and then ultrasonically treat for 0.5 to 1 hour to obtain a 4-formylphenylboric acid solution; add polyethyleneimine to ethanol, stir for 0.5 to 1 hour, and then ultrasonically treat for 0.5 to 1 hour to obtain a polyethyleneimine solution;
[0007] 3. adding the 4-formylphenylboronic acid solution to the polyethyleneimine solution under stirring, stirring for 0.5 to 1 hour, and then ultrasonically treating for 0.5 to 1 hour to obtain a mixed solution;
[0008] 4. Place the polyvinyl alcohol solution obtained in step 2 in an oil bath at a temperature of 88-95°C. Under stirring, add the mixed solution obtained in step 3 dropwise to the polyvinyl alcohol solution. Stir and react for 5-7 hours to obtain a self-healing adhesive, denoted as PVA-4FBA-PEI, which is a light yellow liquid.
[0009] Furthermore, the mass percentage concentration of the polyvinyl alcohol solution in step 2 is 4% to 5%.
[0010] Furthermore, the mass percentage concentration of 4-formylphenylboronic acid in step 2 is 1.5% to 2.5%.
[0011] Furthermore, the mass percentage concentration of the polyethyleneimine in step 2 is 19% to 21%.
[0012] The method for preparing the silicon-based negative electrode of a lithium-ion battery with a self-repairing function of the present invention is carried out according to the following steps:
[0013] 1. Add polyvinyl alcohol to deionized water, stir for 2.5 to 3 hours at a temperature of 75 to 80° C. to obtain a polyvinyl alcohol solution; add 4-formylphenylboric acid to ethanol, stir for 0.5 to 1 hour, and then ultrasonically treat for 0.5 to 1 hour to obtain a 4-formylphenylboric acid solution; add polyethyleneimine to deionized water, stir for 0.5 to 1 hour, and then ultrasonically treat for 0.5 to 1 hour to obtain a polyethyleneimine solution;
[0014] 2. Under stirring conditions, the polyethyleneimine solution is added dropwise to the polyvinyl alcohol solution. After the addition is completed, the stirring is continued for 10 to 15 minutes to obtain a mixed solution A; then, under stirring conditions, the 4-formylphenylboric acid solution is added dropwise to the mixed solution A. After the addition is completed, the stirring is continued for 10 to 15 minutes to obtain a mixed solution B; finally, silicon powder and conductive carbon black are added to the mixed solution B, and the mixture is stirred evenly to obtain a slurry;
[0015] 3. The slurry is coated on a copper foil and dried in an oven at a temperature of 88 to 95°C for 4 to 5 hours to obtain a lithium-ion battery silicon-based negative electrode with self-repairing function, which is recorded as PVA-4FBA-PEI-Si.
[0016] Furthermore, the mass percentage concentration of the polyvinyl alcohol solution in step one is 3.5% to 5%.
[0017] Furthermore, the mass percentage concentration of 4-formylphenylboronic acid in step 1 is 0.4% to 1%.
[0018] Furthermore, the mass percentage concentration of the polyethyleneimine in step one is 1.5% to 3%.
[0019] Furthermore, in step 2, the mass ratio of polyvinyl alcohol in the polyethyleneimine solution, 4-formylphenylboric acid in the 4-formylphenylboric acid solution, polyethyleneimine in the polyethyleneimine solution, silicon powder and conductive carbon black is (0.08-0.083): (0.00078-0.0012): (0.0038-0.0042): (0.15-0.2): 1.
[0020] The adhesive with self-repairing function of the present invention uses 4-formylphenylboronic acid (4FBA) similar to a boat as an intermediate, connects two polymers of polyvinyl alcohol (PVA) and polyethyleneimine (PEI), and forms a double dynamic bond (C=N and BOC) as a lock, which ensures that the polymer chain moves in parallel like an oar while remaining tightly connected to the boat. The parallel movement of the double chain provides an ultra-fast self-healing function, the lock structure ensures the mechanical strength of the adhesive, and the inherent properties of the polymer give the adhesive super flexibility. After the C=N or BOC bond is broken, the dynamic bond can be repaired by the two functional groups C=O and B-OH of 4FBA reacting with the imino (-NH2) functional group of PEI and the hydroxyl (-OH) functional group of PVA respectively. After the adhesive is cut and then touched together, it can be repaired in 2 minutes.
[0021] In the silicon-based negative electrode of the lithium-ion battery with self-repairing function of the present invention, the binder PVA-4FBA-PEI is used to bond silicon powder and conductive carbon black to the copper foil, and the -OH on the surface of the silicon particles will form a large number of hydrogen bonds with the functional groups of -OH and -NH2, thereby further enhancing the adhesion between the binder and the silicon particles, improving the mechanical properties of the electrode piece, and breaking through the difficulty that the traditional self-repairing binder cannot take into account both the rapid self-healing ability and rigidity, effectively dissipating the stress caused by the volume expansion of silicon, thereby avoiding the crushing of silicon particles, effectively inhibiting the volume expansion of silicon, and maintaining the stability of the negative electrode interface and structure.
[0022] The silicon-based negative electrode of the lithium-ion battery with self-repairing function of the present invention has an initial capacity of 1649-2275 mAh / g at a voltage range of 0.01V-1.2V and a current density of 0.2C, and a capacity retention rate of more than 80% after 200 cycles. In addition, the process is simple and has many adaptable systems, which provides a new way for self-repairing binders to improve the performance of silicon-based negative electrodes, has guiding significance for the development of high energy density capacity battery systems, and can be used in the field of silicon-based batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 1 is an infrared spectrum of Si, PVA-4FBA-PEI prepared in Example 1, and PVA-4FBA-PEI-Si prepared in Example 2;
[0024] Figure 2 1 is a stress-strain curve diagram of a CMC binder, a PVA binder, and a binder PVA-4FBA-PEI prepared in Example 1;
[0025] Figure 3 1 is a diagram of the self-repairing of PVA-4FBA-PEI prepared in Example 1 and the tensile test process after self-repairing;
[0026] Figure 4 It is a physical picture of the lithium ion battery silicon-based negative electrode PVA-4FBA-PEI-Si prepared in Example 2, the PVA silicon electrode prepared in Comparative Example 1, and the CMC silicon electrode prepared in Comparative Example 2 after 180° peeling test;
[0027] Figure 5 It is a cycle performance curve diagram of the lithium ion battery silicon-based negative electrode PVA-4FBA-PEI-Si prepared in Example 2, the PVA silicon electrode prepared in Comparative Example 1, and the CMC silicon electrode prepared in Comparative Example 2;
[0028] Figure 6 This is a cycle performance curve of the lithium-ion battery silicon-based negative electrode PVA-4FBA-PEI-Si prepared in Example 3. DETAILED DESCRIPTION
[0029] The beneficial effects of the present invention are verified by the following examples.
[0030] Embodiment 1: The preparation method of the adhesive with self-repairing function of this embodiment is carried out according to the following steps:
[0031] 1. Weigh 1 gram of polyvinyl alcohol, 0.075 gram of 4-formylphenylboronic acid and 1 gram of polyethyleneimine;
[0032] 2. Add the polyvinyl alcohol weighed in step 1 to 20 mL of deionized water, stir for 3 h at 80 ° C to obtain a polyvinyl alcohol solution; add 4-formylphenylboric acid to 5 mL of ethanol, stir for 0.5 h, and then ultrasonically treat for 0.5 h to obtain a 4-formylphenylboric acid solution; add polyethyleneimine to 5 mL of ethanol, stir for 0.5 h, and then ultrasonically treat for 0.5 h to obtain a polyethyleneimine solution;
[0033] 3. adding the 4-formylphenylboronic acid solution to the polyethyleneimine solution under stirring, stirring for 0.5 h, and then ultrasonically treating for 0.5 h to obtain a mixed solution;
[0034] 4. Place the polyvinyl alcohol solution obtained in step 2 in an oil bath at 90°C. Under stirring, add the mixed solution obtained in step 3 dropwise into the polyvinyl alcohol solution. Stir and react for 6 hours to obtain a self-healing adhesive, denoted as PVA-4FBA-PEI, which is a light yellow liquid.
[0035] Embodiment 2: The method for preparing a lithium-ion battery silicon-based negative electrode with self-repairing function in this embodiment is carried out according to the following steps:
[0036] 1. Add 1 gram of polyvinyl alcohol to 24 mL of deionized water, stir for 3 hours at 80°C to obtain a polyvinyl alcohol solution; add 0.08 gram of 4-formylphenylboric acid to 20 mL of ethanol, stir for 0.5 hours, and then ultrasonically treat for 0.5 hours to obtain a 4-formylphenylboric acid solution; add 0.5 gram of polyethyleneimine to 24.5 mL of deionized water, stir for 0.5 hours, and then ultrasonically treat for 0.5 hours to obtain a polyethyleneimine solution;
[0037] 2. Weigh 2.02 g of the polyvinyl alcohol solution prepared in step 1 and add it to a slurry bottle. Under stirring conditions, add 0.2 g of the polyethyleneimine solution prepared in step 1 dropwise to the polyvinyl alcohol solution. After the addition is complete, continue stirring for 10 min to obtain a mixed solution A. Then, under stirring conditions, add 0.2 g of the 4-formylphenylboric acid solution prepared in step 1 dropwise to the mixed solution A. After the addition is complete, continue stirring for 10 min to obtain a mixed solution B. Finally, add 0.1728 g of silicon powder and 0.0288 g of conductive carbon black to the mixed solution B, stir evenly, and obtain a slurry.
[0038] 3. The slurry is coated on a copper foil and dried in an oven at a temperature of 88 to 95°C for 4 to 5 hours to obtain a lithium-ion battery silicon-based negative electrode with self-repairing function, which is recorded as PVA-4FBA-PEI-Si.
[0039] Si, PVA-4FBA-PEI prepared in Example 1 and PVA-4FBA-PEI-Si prepared in Example 2 were subjected to infrared spectroscopy test, and the obtained infrared spectra were as shown in FIG. Figure 1 As shown, from Figure 1 It can be seen that PVA, PEI and 4FBA successfully underwent condensation reaction, and the corresponding bonds were also detected in the prepared PVA-4FBA-PEI-Si negative electrode.
[0040] The stress-strain curve test was carried out with the purchased CMC adhesive, PVA adhesive and PVA-4FBA-PEI adhesive prepared in Example 1. The prepared adhesive was dried at 80°C for 6 h, and then the sample was cut into 40 mm×10 mm (length×width). The tensile tester was used to test the stress-strain curve at 5 mm s -1 The tensile speed is , and the stress-strain test curve is as follows Figure 2 As shown, from Figure 2 It can be seen that compared with the traditional CMC binder and PVA binder, the PVA-4FBA-PEI binder prepared in Example 1 not only has higher stress, but also has excellent strain.
[0041] The PVA-4FBA-PEI prepared in Example 1 was subjected to self-repair and tensile test after self-repair. The test process is as follows: Figure 3 As shown, after the PVA-4FBA-PEI was cut and then touched together, it was completely healed after 2 minutes. At the same time, the self-healed PVA-4FBA-PEI adhesive still maintained excellent ductility. This excellent self-healing ability can play a key role in recovering the breakage and damage of the polymer chain of the adhesive itself caused by the volume expansion of silicon particles during the cycle. Especially in the fast charging process that needs to complete self-healing in a short time, this rapid self-healing ability is even more important. In addition, the excellent ductility of the adhesive after self-repair can provide a stress buffer space for the expansion of silicon particles.
[0042] Comparative Example 1: In this comparative example, PVA is used as a binder to prepare a silicon-based negative electrode for a lithium-ion battery. The specific preparation method is as follows:
[0043] 1. Weigh 1 gram of polyvinyl alcohol and add it to 24 mL of deionized water. Stir for 3 hours at 80°C to obtain a polyvinyl alcohol solution.
[0044] 2. Weigh 2.2 g of the polyvinyl alcohol solution prepared in step 1 and add it to the slurry bottle, then add 0.1728 g of silicon powder and 0.0288 g of polyvinyl alcohol solution, stir evenly, and obtain a slurry;
[0045] 3. The slurry was coated on a copper foil and dried in an oven at 80°C for 4 hours to obtain a silicon-based negative electrode for a lithium-ion battery, which was denoted as PVA-Si.
[0046] Comparative Example 2: In this comparative example, carboxymethyl cellulose (CMC) is used as a binder to prepare a silicon-based negative electrode for a lithium-ion battery. The specific preparation method is as follows:
[0047] 1. Weigh 0.0864 g of carboxymethyl cellulose and add it to 4 mL of deionized water, stir for 0.5 h to obtain a carboxymethyl cellulose solution; then add 0.1728 g of silicon powder and 0.0288 g of silica powder to the carboxymethyl cellulose solution, stir evenly, and obtain a slurry;
[0048] 2. The slurry was coated on a copper foil and dried in an oven at 80°C for 4 hours to obtain a silicon-based negative electrode for a lithium-ion battery, which was denoted as CMC-Si.
[0049] The lithium-ion battery silicon-based negative electrode PVA-4FBA-PEI-Si prepared in Example 2, the PVA silicon electrode prepared in Comparative Example 1, and the CMC silicon electrode prepared in Comparative Example 2 were subjected to a 180° peeling test. The dried electrodes were cut into 40 mm × 10 mm (length × width) pole pieces, and tapes of the same size were pasted on the surface of the pole pieces loaded with active materials. The tensile tester was used to test the strength of the pole pieces at 5 mm s -1 The tape is peeled off from the surface of the electrode at a speed of Figure 4 As shown, from Figure 4 It can be seen that there is almost no peeling of active material on the surface of the lithium-ion battery silicon-based negative electrode PVA-4FBA-PEI-Si electrode, while the active material on the PVA silicon electrode and the CMC silicon electrode is severely lost, indicating that the binder in the lithium-ion battery silicon-based negative electrode PVA-4FBA-PEI-Si prepared in Example 2 has excellent adhesion.
[0050] The lithium-ion battery silicon-based negative electrode PVA-4FBA-PEI-Si prepared in Example 2, the PVA silicon electrode prepared in Comparative Example 1, and the CMC silicon electrode prepared in Comparative Example 2 were subjected to cycle tests. The dried electrode sheets were cut into 12 mm negative electrode sheets, and half cells were assembled. After two cycles of activation at a current of 0.2C, a voltage range of 0.01V to 1.2V, and a current of 0.1C, a cycle performance test was performed. The cycle performance curves of different silicon negative electrodes at 0.2C are shown in FIG. Figure 5 As shown, from Figure 5 It can be seen that at a current density of 0.2C, PVA-4FBA-PEI improves the cycle stability of the silicon negative electrode. The initial capacity at 0.2C is 2274.67 mAh / g, the capacity after 200 cycles is 1867.5 mAh / g, and the capacity retention rate is 82.1%.
[0051] Embodiment 3: The method for preparing a lithium-ion battery silicon-based negative electrode with self-repairing function in this embodiment is carried out according to the following steps:
[0052] 1. Weigh 1 gram of polyvinyl alcohol and add it to 24 mL of deionized water, stir for 3 hours at 80°C to obtain a polyvinyl alcohol solution; add 0.08 gram of 4-formylphenylboric acid to 20 mL of ethanol, stir for 0.5 hour, and then ultrasonically treat for 0.5 hour to obtain a 4-formylphenylboric acid solution; add 0.5 gram of polyethyleneimine to 24.5 mL of deionized water, stir for 0.5 hour, and then ultrasonically treat for 0.5 hour to obtain a polyethyleneimine solution;
[0053] 2. Weigh 2 g of the polyvinyl alcohol solution prepared in step 1 and add it to a slurry bottle. Under stirring conditions, drop 1 g of the polyethyleneimine solution prepared in step 1 into the polyvinyl alcohol solution. After the dropwise addition is completed, continue stirring for 15 min to obtain a mixed solution A. Then, under stirring conditions, drop 1 g of the 4-formylphenylboric acid solution prepared in step 1 into the mixed solution A. After the dropwise addition is completed, continue stirring for 10 min to obtain a mixed solution B. Finally, add 0.1728 g of silicon powder and 0.0288 g of conductive carbon black into the mixed solution B, stir evenly, and obtain a slurry.
[0054] 3. The slurry was coated on a copper foil and dried in an oven at 90°C for 4 hours to obtain a lithium-ion battery silicon-based negative electrode with self-repairing function, which was recorded as PVA-4FBA-PEI-Si.
[0055] The lithium-ion battery silicon-based negative electrode sheet with self-repair function prepared in Example 3 was cut into negative electrode sheets with a side length of 12 mm, and a half-cell was assembled. After two cycles of activation at a current of 0.2C, a voltage range of 0.01V to 1.2V, and a current of 0.1C, a cycle performance test was performed. The cycle performance curves of different silicon negative electrodes at 0.2C are shown in FIG. Figure 6 As shown, from Figure 6 It can be seen that at a current density of 0.2C, PVA-4FBA-PEI improves the cycle stability of the silicon negative electrode. At a current of 0.2C, the initial capacity is 1649.04 mAh / g, and after 150 cycles, the capacity remains at 1424.45 mAh / g, with a capacity retention rate of 84.09%.
[0056] The PVA-4FBA-PEI binder synthesized by the present invention bridges two polymers, polyvinyl alcohol (PVA) and polyethyleneimine (PEI), through an intermediate 4-formylphenylboronic acid (4FBA), so as to achieve mutual parallelism of PVA and PEI polymers, avoid chain entanglement, achieve the unity of self-repairing function and mechanical properties, and has ultrafast self-repairing function. In addition, the excellent performance of the binder can effectively inhibit the volume expansion of silicon, and maintain the stability of the silicon negative electrode structure and the interface.
Claims
1. A method for preparing an adhesive having a self-repairing function, characterized in that The method proceeds as follows:
1. Weigh polyvinyl alcohol, 4-formylphenylboric acid and polyethyleneimine according to the mass ratio of polyvinyl alcohol, 4-formylphenylboric acid and polyethyleneimine of (0.8-1.5):(0.07-0.085):(0.45-1.2); 2. Add the polyvinyl alcohol weighed in step 1 to deionized water, stir at a temperature of 75 to 80° C. for 2.5 to 3 hours to obtain a polyvinyl alcohol solution; add 4-formylphenylboric acid to ethanol, stir for 0.5 to 1 hour, and then ultrasonically treat for 0.5 to 1 hour to obtain a 4-formylphenylboric acid solution; add polyethyleneimine to ethanol, stir for 0.5 to 1 hour, and then ultrasonically treat for 0.5 to 1 hour to obtain a polyethyleneimine solution; 3. adding the 4-formylphenylboronic acid solution to the polyethyleneimine solution under stirring, stirring for 0.5 to 1 hour, and then ultrasonically treating for 0.5 to 1 hour to obtain a mixed solution; 4. Place the polyvinyl alcohol solution obtained in step 2 in an oil bath at a temperature of 88-95°C. Under stirring, add the mixed solution obtained in step 3 dropwise to the polyvinyl alcohol solution. Stir and react for 5-7 hours to obtain a self-healing adhesive, which is recorded as PVA-4FBA-PEI.
2. The method for preparing a self-repairing adhesive according to claim 1, characterized in that The mass percentage concentration of the polyvinyl alcohol solution described in step 2 is 4% to 5%.
3. The method for preparing a self-repairing adhesive according to claim 1 or 2, characterized in that: The mass percentage concentration of 4-formylphenylboronic acid described in step 2 is 1.5% to 2.5%.
4. The method for preparing a self-repairing adhesive according to claim 1 or 2, characterized in that: The mass percentage concentration of the polyethyleneimine described in step 2 is 19% to 21%.
5. A method for preparing a lithium-ion battery silicon-based negative electrode with self-repairing function, characterized in that The method proceeds as follows:
1. Add polyvinyl alcohol to deionized water, stir for 2.5 to 3 hours at a temperature of 75 to 80° C. to obtain a polyvinyl alcohol solution; add 4-formylphenylboric acid to ethanol, stir for 0.5 to 1 hour, and then ultrasonically treat for 0.5 to 1 hour to obtain a 4-formylphenylboric acid solution; add polyethyleneimine to deionized water, stir for 0.5 to 1 hour, and then ultrasonically treat for 0.5 to 1 hour to obtain a polyethyleneimine solution; 2. Under stirring conditions, the polyethyleneimine solution is added dropwise to the polyvinyl alcohol solution. After the addition is completed, the stirring is continued for 10 to 15 minutes to obtain a mixed solution A; then, under stirring conditions, the 4-formylphenylboric acid solution is added dropwise to the mixed solution A. After the addition is completed, the stirring is continued for 10 to 15 minutes to obtain a mixed solution B; finally, silicon powder and conductive carbon black are added to the mixed solution B, and the mixture is stirred evenly to obtain a slurry; 3. The slurry is coated on a copper foil and dried in an oven at a temperature of 88 to 95°C for 4 to 5 hours to obtain a lithium-ion battery silicon-based negative electrode with self-repairing function, which is recorded as PVA-4FBA-PEI-Si.
6. The method for preparing a lithium-ion battery silicon-based negative electrode with self-repairing function according to claim 5, characterized in that: The mass percentage concentration of the polyvinyl alcohol solution described in step one is 3.5% to 5%.
7. The method for preparing a lithium-ion battery silicon-based negative electrode with self-repairing function according to claim 5 or 6, characterized in that: The mass percentage concentration of 4-formylphenylboronic acid described in step 1 is 0.4% to 1%.
8. The method for preparing a lithium-ion battery silicon-based negative electrode with self-repairing function according to claim 5 or 6, characterized in that: The mass percentage concentration of the polyethyleneimine described in step 1 is 1.5% to 3%.
9. The method for preparing a lithium-ion battery silicon-based negative electrode with self-repairing function according to claim 5 or 6, characterized in that: In step 2, the mass ratio of polyvinyl alcohol in the polyethyleneimine solution, 4-formylphenylboric acid in the 4-formylphenylboric acid solution, polyethyleneimine in the polyethyleneimine solution, silicon powder and conductive carbon black is (0.08-0.083): (0.00078-0.0012): (0.0038-0.0042): (0.15-0.2): 1.
Citation Information
Patent Citations
Preparation method of polyethyleneimine-polyvinyl alcohol hydrogel with self-healing performance
CN110698697A